Optimalisasi Limbah Kulit Pisang Sebagai Pupuk Organik Cair untuk Mendukung Pertanian Ramah Lingkungan di Kampung Sungai Gumut, Hulu Selangor, Malaysia - Khansa Ghaida Ainaya; Baeeta Baiysa Bazlaa; Bianca Jazzmine Sharon Pang; Radite Ranggi Ananta (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Sustainable agriculture requires efficient and environmentally friendly use of local resources. One practical effort is converting banana peel waste into liquid organic fertilizer (LOF). Banana peels are rich in macro- and micronutrients but are often discarded, causing potential environmental problems. This community service program was conducted in Kampung Sungai Gumut Tambahan, Hulu Selangor, Malaysia, using an experimental method with a participatory approach. Residents were directly involved in the LOF production process, including chopping banana peels, mixing with molasses, and adding bioactivators (EM4 or probiotics containing Lactobacillus casei). Fermentation was carried out in a 10-liter container for 7–14 days. The resulting fertilizer had a brown color, distinctive fermentation aroma, and homogeneous texture, which improved soil fertility and plant growth. This activity not only reduced dependence on chemical fertilizers but also raised community awareness of organic waste management and created opportunities for small-scale agribusiness development.